Stock Network Stability After Crashes Based on Entropy Method - Yang, Ming-Yuan; Ren, Fei; Li, Sai-Ping (Frontiers in Physics, 2020)
This paper studies the stability of stock networks after crashes based on the entropy method. By measuring network stability using the entropy calculated with the degree distribution, we find that the entropy of a stock network is close to that of the Erdös-Rényi and Watts-Strogatz networks. We further introduce government rescue policies as a natural experiment and use the entropy measurement to study the influence of rescue policies after crashes on the network stability, finding that rescue policies only have short-term effects. Analysis of the relation between stock degrees and government purchasing behavior further confirms the effects of rescue policies on stock network stability.